The significance of c-erb B-2 and p53 immunoreactivity in patients with adenocarcinoma of the esophagus. - Duhaylongsod, F G (1995)
OBJECTIVE: Studies in breast cancer suggest that p53 and c-erb B2 protein overexpression are predictive of outcome. The authors determined whether these molecular markers correlated with treatment response and survival in patients with adenocarcinoma of the esophagus and esophagogastric junction. METHOD: Immunostaining for p53 and c-erb B2 was performed on paraffin-embedded specimens from 42 patients with esophageal adenocarcinoma. All patients received neoadjuvant chemotherapy (cisplatin and fluorouracil [5-FU] x 3 cycles) and irradiation (4500 rads) followed by resection. RESULTS: In this cohort of patients, 79% (33/42) were positive for p53, and 43% (18/42) were positive for c-erb B2. p53 positivity correlated with residual disease in the resection specimen but not with disease-free survival. Although c-erb B2 negatively correlated with residual disease after resection and a 5-year survival of 10%, c-erb B2 positivity was associated with a 5-year actuarial survival of 60%. CONCLUSIONS: Although p53 protein overexpression is commonly observed in adenocarcinoma of the esophagus, its prognostic value appears limited. In contrast, c-erb B2 protein expression predicts a favorable response to therapy and improved survival.